2020
DOI: 10.3390/pharmaceutics12010034
|View full text |Cite
|
Sign up to set email alerts
|

The Polymorphism of Drugs: New Approaches to the Synthesis of Nanostructured Polymorphs

Abstract: Among the significant problems of modern pharmacology are the low solubility and bioavailability of drugs. One way to resolve this problem is to obtain new polymorphic forms of drugs with improved physicochemical properties. Various approaches have been developed with this aim, including the preparation of co-crystals, the use of nanoparticles, or the use of compounds in the form of a salt. A promising direction in pharmacology concerns the production of new stable polymorphic structures. In this mini-review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 49 publications
(73 reference statements)
0
28
0
Order By: Relevance
“…M olecular crystals are ubiquitous in the pharmaceutical industry (1) and show great promise for applications in organic photovoltaics (2); gas adsorption (3); and the food, pesticide, and fertilizer industries (4). Their tendency to exhibit polymorphism, i.e., to exist in multiple crystal structures, on one hand provides a mechanism to tune properties by controlling crystal structure (5) and on the other hand introduces the challenge of synthesizing and stabilizing crystal structures with desired properties (6). While thermodynamic stability at the temperature and pressure of interest is sufficient (although not necessary) to ensure long-term stability, simply understanding thermodynamic stability already poses a formidable challenge.…”
Section: Statistical Mechanics | Machine Learning | Ab Initio Thermod...mentioning
confidence: 99%
“…M olecular crystals are ubiquitous in the pharmaceutical industry (1) and show great promise for applications in organic photovoltaics (2); gas adsorption (3); and the food, pesticide, and fertilizer industries (4). Their tendency to exhibit polymorphism, i.e., to exist in multiple crystal structures, on one hand provides a mechanism to tune properties by controlling crystal structure (5) and on the other hand introduces the challenge of synthesizing and stabilizing crystal structures with desired properties (6). While thermodynamic stability at the temperature and pressure of interest is sufficient (although not necessary) to ensure long-term stability, simply understanding thermodynamic stability already poses a formidable challenge.…”
Section: Statistical Mechanics | Machine Learning | Ab Initio Thermod...mentioning
confidence: 99%
“…Most solid substances in nature exist in the form of crystals, especially for pharmaceuticals. Due to various crystallization conditions, the same pharmaceutical can engender completely different crystals, namely polymorphic phenomenon of drugs [1] , [2] , [3] , [4] . Polymorphism is an aptitude of a substance to crystalize in different crystalline forms which have unique molecular conformation and arrangements in the crystal lattice [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphism is an aptitude of a substance to crystalize in different crystalline forms which have unique molecular conformation and arrangements in the crystal lattice [5] . It has been reported that more than 80 % of pharmaceuticals have polymorph phenomenon [6] .The study of polymorphs of active pharmaceutical ingredients (API) have a crucial implication on the exploitation of new drugs, the optimal control of crystallization process, the patent protection and improvement of physicochemical properties [2] , [7] . So how to realize the control of target polymorph has been gathered more and more focus from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphism, commonly defined as the ability of a substance to exist as two or more crystalline phases that have different arrangements or conformations of the molecules in the crystal lattice [ 1 ] is a phenomenon with particular importance in the pharmaceutical sciences and industry. The differences between polymorphs at the molecular level can manifest themselves in different properties, important in this field, such as hygroscopicity, solubility, thermal stability, rate of dissolution, hardness, chemical reactivity, and many others [ 2 , 3 ]. For the correct design of a pharmaceutical compound, it is, therefore, crucial to control its solid-state form to guarantee its properties.…”
Section: Introductionmentioning
confidence: 99%